2017
DOI: 10.1080/20016689.2017.1335163
|View full text |Cite
|
Sign up to set email alerts
|

2. How is the economic assessment of vaccines performed today?

Abstract: This paper describes how the economic assessment of vaccines is performed today. It discusses why it may be incomplete and explores potential approaches to adjust the analysis to be more comprehensive. Besides helping protect against serious disease, vaccines also help avoid mild disease episodes that may not receive medical attention but which have important societal consequences. They also benefit unvaccinated individuals by reducing disease transmission. Wider societal benefits may extend beyond a decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…We argue in this and previous papers [1,2] that vaccines have a broader impact beyond individual benefit when compared with treatment drugs and therefore, their economic assessment should be evaluated at the higher levels of population and society, rather than the individual and patient levels. In addition, budget impact analysis is crucial for vaccines, as an initial high investment is required that will have no immediate pay-off.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We argue in this and previous papers [1,2] that vaccines have a broader impact beyond individual benefit when compared with treatment drugs and therefore, their economic assessment should be evaluated at the higher levels of population and society, rather than the individual and patient levels. In addition, budget impact analysis is crucial for vaccines, as an initial high investment is required that will have no immediate pay-off.…”
Section: Discussionmentioning
confidence: 89%
“…We have previously outlined the reasons why vaccine benefits could be larger when measured at a population and societal level than when assessed as the sum of benefits to vaccinated individuals only [2]. We suggested that current health economic assessment of vaccines using incremental cost-utility analysis (ICUA) based on quality-adjusted life-years (QALY) gains accrued to individuals are unable to provide a full assessment of the different aspects of value offered by the vaccines to many different stakeholders.…”
Section: Ways Of Moving Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of members under insurance coverage defines the budget made available for investments, and how much they likely want to invest in prevention versus treatment or how much control they want to over infections. In these situations, a CO model can be developed within a specific disease area (influenza, pneumococcal disease, malaria, HPV [36]) or per disease domain (infectious diseases [37], diabetes [38], cancer [39]), when different intervention options exist, precise budgets are known, and the constraints are well specified.…”
Section: Discussionmentioning
confidence: 99%
“…It then reviews the stakeholder list with the focus on the specific benefits sought by each [7,[14][15][16][17]. This is followed by a range of analysis methods for measuring those gains, where we briefly describe how we came to our current findings [18]. In the discussion section, we give examples of the use of a combination of different methods to inform different decision-makers about the full economic value of vaccines.…”
Section: Introductionmentioning
confidence: 99%